EXPLORING THE DRIVERS OF EMPLOYEE PERFORMANCE IN PUBLIC ORGANIZATIONS: EVIDENCE FROM THE DEPARTMENT OF MANPOWER - Apriyani, Putu Reisa; Irwansyah, M. Rudi; Suwena, Kadek Rai (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
This study examined the factors influencing employee performance in the Department of Manpower of Buleleng Regency, Bali. Specifically, it investigated the effects of work discipline, work environment, and work motivation on employee performance. A quantitative approach with a causal research design was applied. The study involved 61 employees consisting of civil servants and contract-based government employees, and a census sampling technique was used to include all members of the population as respondents. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression with SPSS. The results indicate that work discipline, work environment, and work motivation each have a positive and significant effect on employee performance. Simultaneously, these variables significantly contribute to improving employee performance. The findings highlight that strengthening discipline, creating a supportive work environment, and enhancing employee motivation are essential for improving performance and supporting effective public service delivery.